Retropharyngeal soft-tissue mass with multiple cranial neuropathies - Bennour, Anwaar; Dughman, Anas; Elkhashmee, Asmaa (Ibnosina Journal of Medicine and Biomedical Sciences, 2019)
Retropharyngeal lesions have different spectrum of presentations. We herein present a case with step-wise progression of ambiguous symptoms and signs of polycraniopathy, caused by a soft-tissue mass in the retropharyngeal space extending into the cavernous sinus, as detected by magnetic resonance imaging. Initially, he was presented with hemifacial pain and lately progress rapidly to involve all cranial nerves; 3rd through 12th cranial nerves. The differential diagnosis was malignant tumor or aggressive infectious mass, which were excluded by histopathological examination. The diagnosis of inflammatory pseudotumor was a diagnosis of exclusion and decided based on a combination of clinical profile, blood test, radiological, and histopathological results.
Keywords: Inflammatory mass; polycraniopathy; retropharyngeal space